2012
DOI: 10.1111/j.1365-2249.2012.04630.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired function of regulatory T cells in cord blood of children of allergic mothers

Abstract: SummaryAllergy is one of the most common diseases with constantly increasing incidence. The identification of prognostic markers pointing to increased risk of allergy development is of importance. Cord blood represents a suitable source of cells for searching for such prognostic markers. In our previous work, we described the increased reactivity of cord blood cells of newborns of allergic mothers in comparison to newborns of healthy mothers, which raised the question of whether or not this was due to the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 46 publications
5
31
2
Order By: Relevance
“…However, no significant differences in FOXP3 MFI between children from high and low risk were found in a study , while others point to the decrease in Treg function based on the MFI of FOXP3 . These controversial results could be explained by the low number of individuals in the studies or by the different methods used for the quantification of FOXP3 . Based on these studies, we conducted an analysis of the FOXP3 MFI in our samples and, in agreement with the findings regarding Treg numbers in our study, we found a significantly higher FOXP3 MFI in the Treg from the preterm newborns compared with the term newborns.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, no significant differences in FOXP3 MFI between children from high and low risk were found in a study , while others point to the decrease in Treg function based on the MFI of FOXP3 . These controversial results could be explained by the low number of individuals in the studies or by the different methods used for the quantification of FOXP3 . Based on these studies, we conducted an analysis of the FOXP3 MFI in our samples and, in agreement with the findings regarding Treg numbers in our study, we found a significantly higher FOXP3 MFI in the Treg from the preterm newborns compared with the term newborns.…”
Section: Discussionsupporting
confidence: 83%
“…Tregs are a heterogeneous cell population, and many methodological problems arise in the course of their study. Different gating strategies used for the quantification of Tregs (CD4 + CD25 + cells , CD4 + CD25 high , CD4 + CD25 high CD127 low , CD4 + CD25 high FOXP3 ++ , CD4 + CD25 high CD127 low FOXP3 + ) may influence the frequency of these cells .…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of Tregs was estimated in maternal and cord blood by the method described by Hrdy et al [20]. M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 9 …”
Section: Regulatory T Cell (Cd4+/cd25+/cd127-/foxp3) Population In Mamentioning
confidence: 99%
“…Despite an intensive search of prognostic markers for allergy in cord blood (e.g. specific IgE , cytokines , cord blood cell proliferation , proportion and functional capacity of T regulatory cells ), maternal allergy status seems to be the most reliable one .…”
Section: Introductionmentioning
confidence: 99%